2020
DOI: 10.31219/osf.io/cfwvj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental test of the effects of punishment probability and size on the decision to take a bribe

Abstract: Punishment is one of the main methods for preventing corruption. However, studies on the effect of size and probability of punishment on bribe-taking have not yielded conclusive results. We introduce a punishment by a fine or termination of the task, both with varying probabilities, in a laboratory task modeling the decision to take a bribe. The punishment decreased the probability of taking higher bribes, even though the probability of taking lower bribes was unaffected. Participants took fewer bribes when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…We created an on-line version of a sorting task previously used for study of bribe-taking in laboratory settings (Bahník & Vranka, 2022;Vranka & Bahník, 2018). Participants were asked to sort 200 objects appearing one-by-one on their computer screen according to the objects' color.…”
Section: Methodsmentioning
confidence: 99%
“…We created an on-line version of a sorting task previously used for study of bribe-taking in laboratory settings (Bahník & Vranka, 2022;Vranka & Bahník, 2018). Participants were asked to sort 200 objects appearing one-by-one on their computer screen according to the objects' color.…”
Section: Methodsmentioning
confidence: 99%
“…To illustrate, according to the United Nations, the global costs of corruption amount to at least US$2.6 trillion per year 2 . In light of these tremendous costs, a broad array of research has identified multiple factors shaping engagement in bribery and corruption, including social norms [3][4][5] , negative externalities 6,7 , as well as various types of punishment [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%